Duplex ultrasound surveillance for deep vein thrombosis after acute traumatic spinal cord injury at rehabilitation admission. (3rd May 2020) - Hon, Beverly; Botticello, Amanda; Kirshblum, Steven
Abstract : Context/objective: To determine the prevalence of deep vein thrombosis (DVT) detected through routine duplex screening and factors associated with DVT in spinal cord injury (SCI) patients on admission to rehabilitation. Design: Retrospective chart review of medical records. Setting: Acute inpatient rehabilitation. Participants : One hundred and eighty-nine individuals admitted to rehabilitation within 2 weeks of initial traumatic SCI who underwent routine surveillance with duplex scan for DVT. Interventions : Duplex scan of lower extremities. Outcome measures : The dependent variable was positive duplex screening for either any DVT (distal and/or proximal) or proximal DVT. Results: Of the 189 patients, 31 patients (16.4%) had a positive scan for any (proximal and/or distal) DVT, with 9 (4.8%) positive for a proximal DVT and 22 (11.6%) positive for isolated distal DVT. Of those with isolated distal DVT, 31.8% later developed propagation with either proximal DVTs or pulmonary embolism (mean = 22 days). Factors significantly associated with positive duplex scans for any (proximal and/or distal) DVT include more severe neurological injury (AIS A, B or C versus AIS D: χ 2 = 7.1791, df = 1, P = 0.007) and older age (age ≥50 years old: χ 2 = 14.9410, df = 1, P = 0.000). Conclusion: In acute traumatic SCI, older age and more severe neurological impairment (AIS A, B, and C) are independent risk factors for positive duplex screening for any (proximal and/or distal) DVT detected on rehabilitation admission. Individuals with an acute distal DVT have a high likelihood for future thrombus progression. Routine surveillance for these patients may be warranted.